2014
DOI: 10.1071/ah13168
|View full text |Cite
|
Sign up to set email alerts
|

Reflecting on the tensions faced by a community-based multicultural health navigator service

Abstract: The community navigator model was developed to assist four culturally and linguistically diverse communities (Sudanese, Burmese, Pacific Islander Group, Afghani) in south-east Queensland to negotiate the Australian health system and promote health. Using participatory action research, we developed the model in partnership with community leaders and members, the local health department and two non-governmental organisations. Following implementation, we evaluated the model, with the results published elsewhere.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Aboriginal stakeholders, on the other hand, cited lack of support from mainstream services and funding as the main sustainability issues. This disconnect was a reflection of a broader tension between flexibility and structure, which is consistent with findings from Henderson and Kendall (). Fluidity and flexibility characterised the operations of the network.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Aboriginal stakeholders, on the other hand, cited lack of support from mainstream services and funding as the main sustainability issues. This disconnect was a reflection of a broader tension between flexibility and structure, which is consistent with findings from Henderson and Kendall (). Fluidity and flexibility characterised the operations of the network.…”
Section: Discussionsupporting
confidence: 89%
“…Finally, the network provided practical and financial support to its members. Consistent with findings from a community navigator model implemented in Queensland among migrant communities (Henderson & Kendall 2014), flexibility and adaptability were essential characteristics of the network's grassroots approach to practical support delivery; however, MSPs raised issues of risk management and professional boundaries. In addition, the network was based on a volunteer model, and issues of out-of-pocket expenses incurred, availability of volunteers and supervision were also raised, which are consistent with other evidence on volunteer support programmes for people with cancer (Macvean et al 2008).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Evaluation of the program revealed that the navigators felt they were acting as knowledge brokers; that they had been successful in building bridges within the community to improve health literacy and empower local CALD families (Henderson & Kendall, 2011). However, these Australian researchers also recommended maintaining a navigator-centric, grassroots role to avoid the program becoming overly bureaucratic (Henderson & Kendall, 2014).…”
Section: The Patient Navigatormentioning
confidence: 99%
“…The importance of considering context when developing mental health intervention models has been well-established (Henderson & Kendall, 2014; Kakuma et al, 2011; Patel, Abas, Broadhead, Todd, & Reeler, 2001; Shah & Jenkins, 2000; Wiley-Exley, 2006). Although the rationale for the CBR model using task shifting in mental health care is evident, a crucial gap in the literature exists in how to design and implement these mental health care programs and policies that are adaptable to LMIC contexts.…”
Section: Evidence-based Mental Health Intervention For Cbr Workersmentioning
confidence: 99%